Torres, Héctor. (2012). Caracas muerde. Crónicas de una guerra no declarada. Caracas: Puntocero. Reseñado por Octavio Acosta. - Acosta, Octavio (Revista de Investigaciones Literarias, 2015)
Torres, Héctor. (2012). Caracas muerde. Crónicas de una guerra no declarada. Caracas: Puntocero. Reseñado por Octavio Acosta